Birch plywood as gusset plates in glulam frame via mechanical connectors: A combined experimental and numerical study. (15th April 2023) - Wang, Yue; Wang, Tianxiang; Persson, Pontus; Hedlund, Patrik; Crocetti, Roberto; Wålinder, Magnus
Abstract: Birch is a short-lived hardwood species widespread in the Northern Hemisphere. Plywood made from birch has superior mechanical properties compared with that made from most softwoods, which makes it suitable for structural application. In this study, the feasibility of using birch plywood as gusset plates in timber-timber connections is presented. Test frames consisting of birch plywood gussets and glulam beams connected by nails were built and tested. A 2D analytical model based on truss theory and a 3D finite element model were proposed and constructed. Both models showed satisfactory agreements with the test results in terms of stiffness and strength. Tensile failure on the birch plywood gussets along the outermost row of nail holes was observed in the experiment. The observed failure modes and the stress distributions in the 3D numerical model suggest that the spreading angle (Whitmore effective width) theory should be considered in the design phase of birch plywood gusset plates. Besides, a modified spreading angle theory is proposed to both approximate the stress distribution and predict the load-bearing capacity. Highlights: Timber frames built of glulam members and birch plywood gusset plates via nail connections. Typical failure modes found by under-designing the plywood thickness. 2D truss-spring model and 3D numerical model predicting the frame's global stiffness and strength. The Whitmore effective width theory discussed according to the stress distribution in 3D numerical models.